Can environmental awareness explain declining preference for car-based mobility amongst generation Y? An examination of learn to drive behaviours. - Hopkins, D (Elsevier, 2016)
Preference for private motorised vehicles grew substantially through the global North, during the 20th Century. Through this time, licensing, car ownership and vehicle kilometres travelled (VKT) rose across age groups. This had a range of environmental and social equity implications, and ignited a priority for investment in road infrastructure. The system of automobility was cemented by lock-in through the assemblage of infrastructure, technologies, policies and behaviours supporting, and frequently requiring, car based mobility. Yet recent evidence has shown that generation Y (18-35 year olds) are practicing mobility in different ways to earlier generations. Stabilising and declining rates of VKT, licensing and vehicle ownership have been identified in a range of industrialised countries. Adopting an interdisciplinary approach, this paper draws from social practice theory and the theory of planned behaviour, as two traditions to examine what people ‘do’, focusing on the social and the individual respectively. It examines the motivations to learn to drive (LTD), and the preference for driving in New Zealand, a highly car-dependent country, empirically drawing from 51 qualitative interviews. A series of meta-themes are presented and used to explain intended and actual behavioural relating to driving practices. The empirical research finds a diversity of highly nuanced interpretations of LTD, some of which reflect individual characteristics, whilst other interpretations are best understood grounded in a wider societal reading of contemporary trends and meanings. Frequently, justification for learning to drive goes beyond the competency and capacity to drive independently. Implications for policy and planning are detailed.